A teoria dos precedentes em uma época sem precedentes: pandemia de Covid-19, segurança jurídica, integridade e coerência do direito - Cabral, Marília Cruz Monteiro (2023)
The present work aims to analyze the theory of precedents, its genesis, historicity and applicability, as well as the fact that the system of precedents integrates its own subsystem, endowed with differentiated strength, whose hermeneutical gain represents a lot for the legal system, especially when disconnected of the positivist school, to fit into a new model, more coherent and in line with current times. The establishment and observance of judicial precedents, especially when formed in a dialogical way, guarantee coherence and integrity to the legal system, as, according to the notion well summarized in the expression “treat like cases alike”, similar cases must reach similar solutions, or , according to Ronald Dworkin and his chain novel, judicial decisions should not be handed down in isolation, and judges should write down their decisions as if they were writing chapters of a chain novel. Once these fundamental premises are analyzed, questions arise that must be answered throughout the study, focusing on the applicability of precedents in times of crisis. Given the pandemic context experienced due to the spread of the new coronavirus (COVID-19) and the massive judicialization of issues arising from the aforementioned pandemic, a new scenario was imposed for the Judiciary, for magistrates and for the legal system in general. It is important, therefore, to carry out an in-depth analysis of the theory of judicial precedents and their applicability in this moment of crisis, also aiming to analyze various judicial decisions handed down by national judges and courts, defining, above all, how national jurisprudence will be formed. , in this current moment of crisis. The aim is to answer what the cohesion and integrity of Law and the Theory of Precedent itself look like when order breaks down and Law faces a social reality that is completely out of step with other already established situations. It also seeks to answer whether there is a weakening of the Theory of Precedents, due to the absolute break of a previous chain of similar decisions (such as Dworkin's chain novel), and the consequent greater margin of freedom for judges, in the face of of the exceptionality experienced, such as the COVID-19 pandemic. If there is hyper-substantiation of the decisions made during the crisis period, it is understood that there will be no losses, nor the weakening of the legal system.